'Growing together': transnational policy networks and environmental policy change in Costa Rica. (1st January 2015) - Garvin, Theresa; McLennan, Blythe; Calvo–Alvarado, Julio; Sanchez–Azofeifa, Arturo
Costa Rica's Payments for Environmental Services (PES) has been held as a promising option for valuing environmental services in developing countries. We undertook a systematic evaluation of academic and grey literatures and used narrative analysis and policy transfer evaluation to identify the global and local interactions that underpinned the successful implementation of PES. Our work shows that PES was an example of 'growing together' unique to Costa Rica and resulted from complex sharing of policy ideas, knowledge, and institutional and financial arrangements over time. We show that Costa Rica's PES represents a long–term developmental process rather than a simple and straightforward example of policy transfer. We conclude that the development and implementation of programmes valuing environmental services requires a set of underlying social, political, and economic conditions as well as evolving interactions between global and domestic policy arenas specific to each particular nation.